Evaluasi Catchment Area Waduk Batutegi Terhadap Simpanan Air Waduk - LB, Silvia Angelina; Ridwan, Ridwan; Suharyatun, Siti; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2024)
Batutegi Reservoir is one of the important surface water resources in Lampung Province because the potential water it contains has many functions and uses, including as a source of irrigation water for the Sekampung System irrigation area and as a source of water for hydroelectric power plants (PLTA). In order to maintain the sustainability of the reservoir's functions and uses, efforts are needed to maintain the water balance of the reservoir. In this study, an analysis of the physical characteristics and environmental conditions of the Batutegi reservoir catchment area and their influence on reservoir water storage is conducted, aiming to determine the optimum catchment area size that needs to be maintained. Data from various sources, including Landsat 7 and 8 OLI images, are used to evaluate changes in the catchment area conditions during the period of 2004-2023. The research results show that the highest coefficient of determination (R2) between NDVI and NDWI is indicated in land cover conditions with very low density (class 1) at 95.59%, followed by high density (class 4) at 94.80%, low density (class 2) at 92.31%, and medium density (class 3) at 87.58%. The area of land cover with dense vegetation conditions in the Upper Sekampung Watershed as the catchment area of the Batutegi reservoir tends to decrease over time. Analysis of Landsat images using the Normalized Difference Water Index (NDWI) and Normalized Difference Vegetation Index (NDVI) methods can assist in mapping vegetation conditions and the extent of the Batutegi reservoir inundation. Keywords: Catchment Area, Landsat Imagery, NDVI, NDWI, Reservoir.